2021
DOI: 10.1021/acscatal.0c04586
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Selective Oxidation of Benzyl Alcohol via In Situ H2O2 Production over Supported Pd-Based Catalysts

Abstract: Bimetallic Pd-Fe catalysts supported on TiO 2 are shown to be highly effective toward the selective oxidation of benzyl alcohol to benzaldehyde via the in situ production of H 2 O 2 from molecular H 2 and O 2 , under conditions where no reaction is observed with molecular O 2 alone. The rate of benzyl alcohol oxidation observed over supported Pd-Fe nanoparticles is significantly higher than those of either Pd-Au or Pd-only analogues. This enhanced activity can be attributed to the bifunctionality of the Pd-Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 72 publications
(131 reference statements)
6
63
0
Order By: Relevance
“…29 In keeping with numerous studies, [32][33][34] . This is in keeping with our previous studies 24,36 and may be ascribed to a combination of (i) the reaction conditions chosen to…”
Section: Resultssupporting
confidence: 88%
“…29 In keeping with numerous studies, [32][33][34] . This is in keeping with our previous studies 24,36 and may be ascribed to a combination of (i) the reaction conditions chosen to…”
Section: Resultssupporting
confidence: 88%
“…Alternatively, the direct synthesis of H 2 O 2 from molecular H 2 and O 2 has the potential to avoid many of the drawbacks associated with the anthraquinone oxidation process, allowing for the on-site manufacture of dilute streams of H 2 O 2 [5]. Additionally, the in-situ production of H 2 O 2 has been demonstrated to offer improved activity, compared to the use of preformed H 2 O 2 , in a range of selective chemical transformations, under reaction conditions where H 2 O 2 is considered highly unstable [6][7][8][9][10]. With the enhanced performance of the in-situ approach possibly related to the avoidance of the acid stabilisers that are used to inhibit preformed H 2 O 2 decomposition during transport and storage.…”
Section: Introductionmentioning
confidence: 99%
“…Several research efforts on benzyl alcohol oxidation studies have revealed important factors affecting reaction activity such as type and catalyst loading, H 2 O 2 : benzyl alcohol molar ratio, reaction duration and temperature [2,13,[30][31][32]. To achieve optimum performance, these key effective factors were investigated in detail as follows.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Reaction duration is one of the most effective reaction factors, which play an important role in the oxidation of benzyl alcohol [4,13,31,34]. Table 3 shows the conversion and selectivity values of the reaction at 5, 6, 7 and 8 h. Prolonged reaction duration increases the conversion percentage from 74 to 89% but decreases the selectivity from 92 to 85%, respectively.…”
Section: Effect Of the Reaction Duration And Stability Of The Catalystmentioning
confidence: 99%
See 1 more Smart Citation